KLASIFIKASI PENENTUAN PENERIMA PROGRAM KELUARGA HARAPAN (PKH) MENGGUNAKAN ALGORITMA SUPPORT VECTOR MACHINE (SVM) PADA KANTOR DINAS SOSIAL LOMBOK TIMUR - imam fathurrahman; fathurrahman fathurrahman (Infotek: Jurnal Informatika dan Teknologi, 2020)
The Family of Hope Program (PKH) is a program of giving cash to Very Poor Households (RTSM) based on established terms and conditions. Where PKH was implemented in Indonesia in 2007, but in East Lombok PKH was only implemented in 2011. However, judging from the data of PKH recipient members, there are still many RTSM who do not get the PKH assistance. This situation identified the data collection method and the determination of priorities that were not yet on target. From these problems, it is necessary to utilize data mining techniques using the support vector machine (SVM) algorithm in determining PKH recipients. After testing 4 times using different K-Fold Validation on the cross validation operator. K-Fold Validation functions to divide the amount of training data and testing data on the data being tested. Then the accuracy results that have been tested are 95.41%.DOI : 10.29408/jit.v3i1.1802